A case report of recurrent Well’s syndrome masquerading as cellulitis - Anum Qureshi; Jasmine Manley; Tristan Flack; Mark H. Lowitt (Journal of Community Hospital Internal Medicine Perspectives, 2021)
Eosinophilic cellulitis (Well’s syndrome) is a rare relapsing inflammatory disorder characterized by infiltration of eosinophils into the dermis. Although rare, WS should be considered in patients with a history of asthma and skin lesions that are resistant to antibiotic therapy. We report a case of recurrent WS. A 67-year-old woman with a history of asthma presented with a longstanding left pretibial ulcer with surrounding erythema, pain, and serous drainage, which had failed treatment with oral and parenteral antibiotics. Skin biopsy revealed eosinophilic cellulitis. Rapid improvement occurred with systemic steroid treatment; however, recurrent disease in the perineum developed as corticosteroids were tapered.